Achievements and Prospects of Vaccination against Human Papillomavirus Infection and Associated Diseases - G. N. Minkina (Эпидемиология и вакцинопрофилактика)
Relevance. The past decade has been marked by rapid advances in the prevention of human papillomavirus (HPV) infections and associated diseases.Aims. To sum up the accumulated experience and evidence base of the impact of national HPV vaccination programs on the prevalence of HPV infections, the incidence of genital warts and precancerous cervical lesions. 3.Conclusions. To reach its full potential and have a greater and earlier impact on the population, gender-neutral and, if possible, multi-cohort HPV vaccination should be included in the national immunization calendar.